2019
DOI: 10.7150/jca.30975
|View full text |Cite
|
Sign up to set email alerts
|

Associations of mRNA expression of DNA repair genes and genetic polymorphisms with cancer risk: a bioinformatics analysis and meta-analysis

Abstract: A systematical bioinformatics and meta-analysis were carried out to establish our understanding of possible relationships between DNA repair genes and the development of cancer. The bioinformatics analysis confirmed that lower XPA and XPC levels and higher XPD , XPF , and WRN levels were observed in 19 types of cancer, and subsequently results indicated that elevated XPA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…A recent meta-analysis demonstrated that ERCC2 rs13181 GG genotype has a positive prognostic value in predicting the overall survival of HCC patients [56]. On the other hand, rs238406 TT genotype was associated with an increased overall cancer risk [60]. In our study, both SNPs were associated with liver cirrhosis development.…”
Section: Discussionsupporting
confidence: 57%
“…A recent meta-analysis demonstrated that ERCC2 rs13181 GG genotype has a positive prognostic value in predicting the overall survival of HCC patients [56]. On the other hand, rs238406 TT genotype was associated with an increased overall cancer risk [60]. In our study, both SNPs were associated with liver cirrhosis development.…”
Section: Discussionsupporting
confidence: 57%
“…Clinical studies have found that different individuals with the same clinical characteristics show great heterogeneity in clinical manifestations, treatment sensitivity, disease recurrence, and survival outcomes. We have previously reported on individual differences in genetic susceptibility, (31)(32)(33). However, a large number of research results are inconsistent, and there is no consensus on whether differences in DNA repair gene expression can be used as prognostic indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the most comprehensive meta-analysis for rs10817938 and rs2808668 and cancer risk (33 types of cancer were examined) showed that harbouring rs10817938 homozygous CC genotype, C allele, and CC/CT genotype in a dominant setting associates with an increased overall cancer risk, with a specific association with digestive system cancers. In contrast, there was no association with overall cancer risk for rs2808668, albeit subgroup analysis revealed a decreased risk in the majority of cancers examined, with the exception of digestive system cancer [156]. In addition, this SNP interacts with environmental factors, such as alcohol consumption in gastric cancer (GC), and clinical-pathological characteristics, such as tumour size, metastatic status at onset, and mitotic index in gastrointestinal stromal cancer [157,158].…”
Section: Xpa Polymorphisms and Cancer Incidence And Treatment Outcomementioning
confidence: 99%
“…Changes in the expression level of XPA are assumed to significantly contribute to cancer risk, disease prognosis and treatment outcome. To identify the potential role of XPA mRNA expression in different cancer types, Wu et al [156] used two approaches: (i) comparison of the XPA mRNA expression in 13 types of cancers from the RNA sequencing dataset platform GENT (Gene Expression Database of Normal and Tumor Tissues, http://medical-genome.kribb.re.kr/GENT/) and (ii) freely available information on XPA expression in 19 types TCGA (The Cancer Genome Atlas) datasets and their normal controls from ONCOMINE, a cancer microarray database and web-based data-mining platform (https://www.oncomine.org/). These approaches revealed decreased expression of XPA in a range of tumours, including bladder, kidney, liver, lung (also seen in [195]), prostate, and stomach cancers.…”
Section: Xpa Expression As a Cancer Risk Factor And Its Prognostic And Predictive Valuementioning
confidence: 99%